The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1010539516645156
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Obesity Trends in Tonga Over 40 Years

Abstract: Disparate population surveys of type 2 diabetes mellitus (T2DM) have been conducted in Tonga for 4 decades. This study standardizes these surveys to enable assessment of T2DM and obesity trends in Tongans aged 25 to 64 years over 1973-2012, and projects T2DM prevalence to 2020 based on demographic and population weight changes. Eight surveys were standardized to the nearest census to produce nationally representative estimates. Linear period trends and prevalence projections to 2020 were produced using random-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…In Tonga, BMI increases explained 76% (men) and 73% (women) of T2DM prevalence increases over 1973–2012 [23]. BMI increases in Samoa, Fiji [22] and Tonga [23] have been attributed to changes in way of life, including a shift away from farming and fishing towards more sedentary occupations; and increased consumption of energy dense imported foods [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In Tonga, BMI increases explained 76% (men) and 73% (women) of T2DM prevalence increases over 1973–2012 [23]. BMI increases in Samoa, Fiji [22] and Tonga [23] have been attributed to changes in way of life, including a shift away from farming and fishing towards more sedentary occupations; and increased consumption of energy dense imported foods [24]. …”
Section: Discussionmentioning
confidence: 99%
“…16 Similar observations were reported in other Pacific, African and Caribbean countries. 13,[17][18] In contrast, Lin et al 19 reported high prevalence of diabetes in both rural and urban areas in Pacific Tongans. This suggests adoption of new lifestyle which is closely associated with urbanisation in certain countries might not be applicable to some indigenous populations who are at high risk of diabetes irrespective of the rural-urban status.…”
Section: Discussionmentioning
confidence: 95%
“…It is apparent that in recent STEPS surveys in Fiji (2011), Samoa (2013) and Tonga (2012), the incorrect glucose cut‐off point was applied, and the T2DM prevalence reported were erroneously inflated to approximately double the actual T2DM prevalence had the correct glucose cut‐off point been applied (Table ; Figure ). When correct plasma cut‐off points are applied, changes in T2DM prevalence over the survey periods for each country are as follows: (i) Fiji, from 16.0 % to 15.6 % (−0.4 percentage points) over 2002–11 (instead of the reported +13.6 percentage points); (ii) Samoa from 21.5 % to 24.3 % (+2.8 percentage points) over 2002–13 (instead of +24.3 percentage points); and (iii) Tonga, from 22.4 % (including estimated all known T2DM) to 19.0 % (−3.4 percentage points) over 2004–12 (instead of +18 percentage points) …”
Section: Type 2 Diabetes Mellitus Prevalence In Adults Aged 25–64 Yeamentioning
confidence: 99%
“…For these POC glucose meters, the whole blood glucose concentration is multiplied by 1.11 to express the glucose concentration as plasma equivalent, in accordance with recommendations from the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC), first published in 2001 15 and repeated in 2005. 16 It is apparent that in recent STEPS surveys in Fiji (2011), 1,2 Samoa (2013) 3,4 and Tonga (2012), 5,6 the incorrect glucose cut-off point was applied, and the T2DM prevalence reported were erroneously inflated to approximately double the actual T2DM prevalence had the correct glucose cut-off point been applied ( 19.0 % (À3.4 percentage points) over 2004-12 (instead of +18 percentage points). 19 Some of the T2DM prevalence rates reported from other Pacific Island STEPS surveys 20 require further scrutiny where T2DM prevalence appears inordinately high and/or a considerable increase in prevalence is apparent compared with previous surveys.…”
mentioning
confidence: 99%
See 1 more Smart Citation